2017
DOI: 10.1192/bjp.bp.116.182915
|View full text |Cite
|
Sign up to set email alerts
|

Physical illness in those with mental illness: Psychiatric services need to change focus

Abstract: SummaryThose with mental illness die prematurely. One reason may be that psychiatrists are overly concerned with risk, focusing too much on this aspect of practice and neglecting the physical health needs of our patients. We need to reconsider how we approach our patients and their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“… 20 On these grounds, the PHQ-9 was also used as a depression screening and outcome measure in the previous DEPSCREEN-INFO trial and was well accepted by patients and physicians. 12 Given that the DEPSCREEN-INFO trial indicated that a 1-month follow-up may be too short to reflect all effects of the feedback intervention, the primary outcome for this study is depression severity after 6 months.…”
Section: Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“… 20 On these grounds, the PHQ-9 was also used as a depression screening and outcome measure in the previous DEPSCREEN-INFO trial and was well accepted by patients and physicians. 12 Given that the DEPSCREEN-INFO trial indicated that a 1-month follow-up may be too short to reflect all effects of the feedback intervention, the primary outcome for this study is depression severity after 6 months.…”
Section: Methods and Analysismentioning
confidence: 99%
“…No major risks for serious adverse events caused by the application of the feedback intervention were identified in the DEPSCREEN-INFO trial. 12 Numerous studies have shown that depression screening does not cause suicidality or self-harm. 33 34 It seems that questions about suicidality lower the risk of suicide.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
See 2 more Smart Citations
“…There are high levels of comorbid mental illness among consumers in generalist hospital wards (Daly ; Hert et al . ).…”
Section: Introductionmentioning
confidence: 99%